Assessment of litter prevalence of Mycoplasma hyopneumoniae in preweaned piglets utilizing an antemortem tracheobronchial mucus collection technique and a real-time polymerase chain reaction assay. (September 2015) - Vangroenweghe, Frédéric; Karriker, Locke; Main, Rodger; Christianson, Eric; Marsteller, Thomas; Hammen, Kristin; Bates, Jessica; Thomas, Paul; Ellingson, Josh; Harmon, Karen; Abate, Sarah; Crawford, Kimberly
The swine industry currently lacks validated antemortem methods of detecting baseline herd prevalence of Mycoplasma hyopneumoniae . The focus of our study was to evaluate alternative antemortem detection techniques and to determine baseline litter prevalence in preweaned pig populations utilizing the selected technique and a real-time polymerase chain reaction (qPCR) assay. Preliminary data was analyzed on weaned piglets with evidence of respiratory disease ( n = 32). Five sample types (antemortem nasal swab, tracheobronchial mucus, postmortem deep airway swab, bronchoalveolar lavage, and lung tissue) were collected from each pig. Individual samples were tested for M. hyopneumoniae using qPCR. Compared to nasal swabs, tracheobronchial mucus demonstrated higher test sensitivity ( P < 0.0001). Tracheobronchial mucus was collected from apparently healthy preweaned piglets ( n = 1, 759; sow farms 1–3) and preweaned piglets exhibiting signs of respiratory disease ( n = 32; sow farm 4), ranging in age from 12 to 25 days. Samples from sow farms 1–3 were pooled into 2 groups of 5 per litter ( n = 360 pools from 180 litters), and qPCR was utilized to analyze each pool. A qPCR-positive result, threshold cycle <37, from either pool designated the litter positive for M. hyopneumoniae . Two out of 180 litters revealed a positive result (1.1%). Individual qPCR assays were run on the samples collected from sow farm 4. Five out of 30 samples revealed a positive result (16.7%). Tracheobronchial mucus collection in combination with qPCR is a sensitive antemortem sampling technique that can be used to estimate the prevalence of M. hyopneumoniae in preweaned pigs, thus providing insight into the infection dynamics across the entire farrow-to-finish process.